Berlin 1938: Aus den Lehrjahren des Elemér Pólay - Jakab, Éva (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The study by the Hungarian Romanist Elemér Pólay on the ‘Ns legal concept and Roman law’ is to be regarded as a valuable source of contemporary and scientific history. The author offers a good overview of Nazi legislation that objectively informs Hungarian readers then and now, but he takes a critical look at some of the results of this legislation as well. Pólay demonstrates the endangered situation of Roman law: he courageously fights for the importance of the discipline to which he has felt called since his youth. His arguments in the context of his stay in Berlin and his contacts with Paul Koschaker also deserve international interest. If one compares Koschaker’s ‘Krise des römischen Rechts‘ (‘Crisis of Roman Law’) with Pólay’s ‘Ns Legal Concept and Roman Law’, striking parallels, but also differences, can be identified. Pólay makes arguments that can also be found in Koschaker’s writing. These indirect allusions show that Pólay was integrated in Koschaker’s seminary, knew his opinion, and internalized it. However, Pólay also sharply criticized Nazi legal figures. It is likely that Pólay was encouraged by him to put these thoughts on paper and that he witnessed relevant critical debates in Koschaker's environment. In Pólay's lines, Koschaker's convictions as a private individual should be echoed, although Koschaker, as a Berlin professor, did not dare to advocate these theses in public.